2018
DOI: 10.1021/acsaem.8b00222
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-Printed Triple Cation Perovskite Solar Cells

Abstract: Noncontact inkjet printing offers rapid and digital deposition combined with excellent control over the layer formation for printed perovskite solar cells. In this work, inkjet printing is used to deposit triple cation perovskite layers with 10% cesium in a mixed formamidinium/methylammonium lead iodide/bromide composite for solar cells with high temperature and moisture stability. A reliable process control over a wide range of perovskite layer thickness from 175 to 780 nm and corresponding grain sizes is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 35 publications
7
178
0
Order By: Relevance
“…The PCEs achieved here belong to the highest values reported for vacuum-processed NiO x HTLs without additional doping (besides the intrinsic defect doping), thus highlighting the high quality of the electron beam evaporated NiO x layer. [67][68][69][70][71] Indeed, contact angle measurements confirm a good wettability (contact angle < 90°) for the triple-cation perovskite solution on the smooth NiO x surface without spreading of the droplet (see Figure S12 in the Supporting Information). In particular, for the inkjet-printed devices, the advance from the latest reported records with stabilized PCEs of up to 18.3% for singlecation and 12.9% for triple-cation is remarkable and indicates the great promise of this technology.…”
Section: Nickel Oxide Hole Transport Layers For Efficient Perovskite-mentioning
confidence: 84%
See 1 more Smart Citation
“…The PCEs achieved here belong to the highest values reported for vacuum-processed NiO x HTLs without additional doping (besides the intrinsic defect doping), thus highlighting the high quality of the electron beam evaporated NiO x layer. [67][68][69][70][71] Indeed, contact angle measurements confirm a good wettability (contact angle < 90°) for the triple-cation perovskite solution on the smooth NiO x surface without spreading of the droplet (see Figure S12 in the Supporting Information). In particular, for the inkjet-printed devices, the advance from the latest reported records with stabilized PCEs of up to 18.3% for singlecation and 12.9% for triple-cation is remarkable and indicates the great promise of this technology.…”
Section: Nickel Oxide Hole Transport Layers For Efficient Perovskite-mentioning
confidence: 84%
“…Prior to the deposition of the HTL, an additional cleaning step in oxygen plasma for 3 min was performed. [67,69] Solar Cell Fabrication: In order to get working solar cells, a 25 nm thick C 60 fullerene layer (Alfa Aesar, 98%, CAS: 99685-96-8) followed by a 3 nm thick bathocuproine (Luminescence Technology, CAS: 4733-39-5) was thermally evaporated as the electron transport layers on top of the absorbers. As raw material, green NiO pieces (99.995%, Alfa Aesar, CAS: 1313-99-1) with a diameter of around 10 mm were used.…”
Section: Methodsmentioning
confidence: 99%
“…[84,85] Inkjet printing of efficient OPV has been demonstrated in 2007. [91] A strong influence of the thickness on the perovskite absorber (affecting properties such as grain size) was observed (see Figure 3b-d). In 2014, Yang et al utilized inkjet printing to fabricate HTL-free and metal-electrode-free PSC in a twostep process by inkjet printing MAI on top of a spin-coated PbI 2 layer.…”
Section: Inkjet Printingmentioning
confidence: 90%
“…For example, by using a C 60 interlayer between the TiO 2 and the one-step-printed MAPbI 3 , Liang et al demonstrated a PCE of 17.0% for a 0.04 cm 2 solar cell and 13.3% for a 4 cm 2 (active area) PSC. [91] Copyright 2108, the American Chemical Society. In this manner, large perovskite grains were obtained and the resulting solar cells showed a PCE of 18.6% for a 0.04 cm 2 large solar cell, and 17.7% for larger Adv.…”
Section: Inkjet Printingmentioning
confidence: 99%
See 1 more Smart Citation